6-3.98=x

Simple and best practice solution for 6-3.98=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-3.98=x equation:


Simplifying
6 + -3.98 = x

Combine like terms: 6 + -3.98 = 2.02
2.02 = x

Solving
2.02 = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
2.02 + -1x = x + -1x

Combine like terms: x + -1x = 0
2.02 + -1x = 0

Add '-2.02' to each side of the equation.
2.02 + -2.02 + -1x = 0 + -2.02

Combine like terms: 2.02 + -2.02 = 0.00
0.00 + -1x = 0 + -2.02
-1x = 0 + -2.02

Combine like terms: 0 + -2.02 = -2.02
-1x = -2.02

Divide each side by '-1'.
x = 2.02

Simplifying
x = 2.02

See similar equations:

| (y-12)+(3y-8)=180 | | 28a^2-192a-28=0 | | 7w-5=3w+11 | | 9x+29=93-5x | | 10-(-10)-7-5=x | | 8.5x-3.5x=-94 | | (-11)-8+1-(-6)=x | | 4x+2=x-11 | | (-3)+5+(-5)+12=x | | x/2+3=1/2 | | 6+(-7)+(-5)-(-2)=x | | 6y=45-3y | | 7+(-1)+12-7=x | | (-11)-(-14)+7=x | | 9+6(2)7n= | | 0.5x-1.4=1.1 | | (-7)-(-2)-9=x | | -6-1=-32y+32 | | 16-(-13)-(-5)=x | | 6(y-4)=5[17-3(2y-13)] | | 4-5+7k=33 | | -9-200x+(0.015)(100)= | | (-16)-6+(-5)=x | | 12+0.4(x-2)=10 | | 6(x+2)+4=-6 | | 52x=104 | | 8y-5=6y+7 | | -33m-14=85 | | 5x+5x+3+8=5x+4+4x | | -r+259=-124 | | -2x^2+12x+3=0 | | 3(3+2r)=5-6(r+2) |

Equations solver categories